TINJAUAN DATA SOSIAL UNTUK ENTRY DATA IDENTITAS PASIEN DI RSI JAKARTA SUKAPURA - Lisa Anggun Magdalena Gea; Noor Yulia (Bajang Institute, 2023)
Social data is used to complete the RME when officers identify new patients into the medical record database. social data helps fill in electronic medical record data. The purpose of this study is to review filling in social data to complete the identity of patients at the Islamic Hospital of Jakarta Sukapura. The research method used descriptive method with quantitative analysis of 81 samples of new outpatient identities. The results of the study There are already standard operating procedures for outpatient registration of new patients, the average completeness of social data for new patients is 62 samples (76%) and 19 samples are incomplete (24%), complete average RME data is complete 65 samples (80%) and incomplete 16 samples (20%). the filling of social data and RME is not in accordance with the minimum service standards set by PERMENKES, which is 100% filled. social data does not include all patient identity data in the RME. Identity data in RME is more complete than social data, in social data there are 21 items while in RME there are 25 items. Conclusion: social data has not been able to fully assist officers in completing electronic medical record patient identity data.